THE RESEARCH ON LISTENING CONDUCTED BY THE STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM - Susanto, Harry; Salam, Urai; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research attempts to identify the thesis topics on listening: particularly it focus on, methods, research focus (teaching technique and media) and the educational level within the thesis. The appropriate method of this research is the descriptive method in which it provides information about the thesis written by English department students. The students? theses on listening are selected based on ranging year from 2010 to 2014. The findings shows that (1) Classroom Action research is the most preferable method (2) 13 studies focused on teaching media and nine others on teaching technique, two theses without specific focus and a thesis focused on both. (3) 11 studies conducted in the senior high, eight were in the junior high and while playgroup, elementary and university share the exact same number, two theses on each educational level. This research may help the other students decide other potential methods, focuses and educational level as their main concerns for their future studies.   Keywords: thesis on listening, research methodologies, focus of research, educational levels. Abstrak: Penelitian ini bertujuan untuk mengidentifikasi tesis dalam menyimak: metode, fokus penelitian (teknik mengajar dan media) dan tingkat pendidikan di dalam tesis. Metode yang tepat dalam penelitian ini adalah metode deskriptif yang memberikan informasi tentang kondisi dan peristiwa yang terjadi di masa sekarang. Tesis dalam menulis dipilih di mulai dari tahun 2010 hingga 2014. Temuan penelitian ini adalah (1) Penelitian Tindakan Kelas adalah metode yang paling banyak (2) 13 penelitian difokuskan pada media pengajaran dan sembilan  penelitian pada media pembelajaran, sementara tiga tesis difokuskan pada teknik mengajar dan teknik penbelajaran, ada dua tesis tanpa fokus pengajaran dan satu tesis memfokuskan pada teknik dan media pembelajaran (3) 11 penelitian dilakukan di SMA, delapan berada di SMP, sementara untuk tingkat TK, SD dan univesitas masing2 terdapat dua tesis. Penelitian ini diharapkan dapat membantu siswa lain memutuskan metode-metode potensial lainnya, teknik dan media pembelajaran serta tingkat pendidikan karena untuk penelitian lebih lanjut. Kata Kunci:   tesis mendengarkan, metodologi penelitian, fokus penelitian, dan tingkat pendidikan